Preparation and characterization of steamed buns incorporated with cross-linked resistant starch type-4 - Abdul Shukri, Farah Syahirah (2017)
Steamed buns were prepared from different percentages (5%, 10%, and 15%) of three types of cross-linked (CL) starches as wheat flour substitution. The objectives of the research were to study effects of three types of CL starches at different levels (5%, 10%, and 15%) on physicochemical properties and sensory acceptance of steamed buns. The storage study was also conducted to determine the shelf life of the fortified steamed buns at refrigeration temperature (±4°C) for 15 days. The study was carried out to evaluate the potential of RS as a dietary fibre in a conventional steamed bun and its potential for health benefits in food application without affecting the appearances of the steamed buns produced. Three types of CL starches which were cross-linked potato starch (CLPS), cross-linked corn starch (CLCS) and cross-linked tapioca starch (CLTS) were produced by cross-linking with a combination of 12% sodium trimetaphosphate and sodium tripolyphosphate (99:1) for 3 h at 45 °C under pH 11.5. Cross-linking process demonstrated significant increase of RS and TDF content in the three different types of CL starches (CLPS, CLCS and CLTS) more than 70% compared to their native starches. For pasting properties, the viscosity of the CL starches displayed a significant decrease as CL starches resist swelling much greater than their natives starches. In contrast, CL starches had higher transition temperatures but lower enthalpy values of gelatinization as compared to their native starches for the thermal properties. The gelatinization enthalpy of the CLCS was 13.03 J/g which was lower than CLPS and CLTS (15.27 J/g and 16.21 J/g, respectively). The cooked steamed buns were characterized by physicochemical and sensory properties. The volumes were positively correlated with the protein content, indicating lower gluten formation in fortified steamed buns. Fortification of CL starches in steamed buns had minimized the distribution of air cells in the buns, lowered the volume of expansion by making them slightly denser. The CL starch-enriched steamed buns had high TDF and RS content (up to 3.8% and 3.05% respectively), improved textural properties and similar sensory acceptance as the control. The addition of 5%, 10% and 15% substitution of CL starch showed no statistically significant on the moisture content of steamed buns but was observed to increase slightly around 0.27-0.7% from the positive control (PF) for CL potato starch enriched steamed buns. Among all the starches, CL corn and CL potato starches had a better overall effect on the physicochemical and textural properties, as well as the sensory acceptance of the steamed buns. For the microbial storage study, the aw and pH of the fortified steamed buns showed no significant changes. The steamed bun samples kept for 15 days still had total plate count lower than 4.00 log CFU/g which implied that they were safe to consume. Formation of molds only been detected in some samples on day 13 and day 15. The results indicated that CL starches, particularly CLCS and CLPS have potential to improve the nutritional properties of steamed buns with less detrimental sensorial and textural effects as compared to whole wheat flour.